The Role of Betengan and Gobak Sodor Traditional Games in Building Student’s Social Characters (Journal of Physical Education and Sports, 2019)
This study discusses the role of betengan and gobak sodor traditional games that implemented as physical education learning materials in school to build student’s social characters, such as honesty, discipline, hard work, sportsmanship, communicative, cooperation, and responsibility. This study aims to analyze the differences of the characters that formed through both of these two traditional games as seen from the student’s gender. This study is a descriptive qualitative type of research. The data resource is 7th-grade students of Islamic Integrated Junior High School Ihsanul Fikri Magelang in the year of 2017/2018 in a total of 60 students. The subjects are ten male students, as well as ten female students. The result obtained in this research shows that all students can bring up the character indicators during playing betengan and gobak sodor games that implemented in PE learning process. The conclusion is that betengan and gobak sodor traditional games that implemented as a learning process in school can build student’s social characters if done continuously. In betengan game, the male student group is better in showing up honesty, discipline, and sportsmanship character. The female student group is better in showing up communicative, cooperation, and responsibility character. In the gobak sodor game, the male student group is better in showing up honesty, discipline, hard work, sportsmanship, communicative, and responsibility character.